Physician Specialty and Office Visits Made by Adults With Diagnosed Multiple Chronic Conditions: United States, 2014-2015 - Ward, Brian W. (Public Health Rep, 2020)
OBJECTIVES: Adults with multiple chronic conditions (MCCs; ≥2 chronic conditions) account for a substantial number of visits to health care providers. The complexity of a patient’s care, including the number of chronic conditions, may differ by physician specialty. The objectives of this study were to (1) examine differences in physician office visits among adults with MCCs by physician specialty and (2) identify the types of MCC dyads (combinations of 2 chronic conditions) most common among visits to office-based physicians. METHODS: We used data from the 2014-2015 National Ambulatory Medical Care Survey (unweighted analytic sample, n = 61 682), a nationally representative survey of physician office–based ambulatory visits, to examine differences in physician office visits among adults with MCCs by physician specialty. We also identified the most commonly observed MCC dyads among these visits. RESULTS: During 2014-2015, 40.0% of physician office visits were made by adults with MCCs. Compared with visits for all specialties combined (40.0%), a significantly higher percentage of physician office visits among adults with MCCs were to specialists in cardiovascular disease (74.7%) and internal medicine (57.6%). For all physician specialties except psychiatry, the MCC dyads of hyperlipidemia and hypertension and diabetes and hypertension were among the most commonly observed MCC dyads among visits made by adults with MCCs. CONCLUSIONS: Awareness of these findings may help specialists improve care for adults with MCCs. The recognition among physicians of common MCC dyads is relevant to the care management of persons with MCCs.